Mesenchymal Stromal Cell-Seeded Biomimetic Scaffolds as a Factory of Soluble RANKL in Rankl-Deficient Osteopetrosis. (5th September 2018) - Menale, Ciro; Campodoni, Elisabetta; Palagano, Eleonora; Mantero, Stefano; Erreni, Marco; Inforzato, Antonio; Fontana, Elena; Schena, Francesca; van't Hof, Rob; Sandri, Monica; Tampieri, Anna; Villa, Anna; et al.
Abstract: Biomimetic scaffolds are extremely versatile in terms of chemical composition and physical properties, which can be defined to accomplish specific applications. One property that can be added is the production/release of bioactive soluble factors, either directly from the biomaterial, or from cells embedded within the biomaterial. We reasoned that pursuing this strategy would be appropriate to setup a cell-based therapy for RANKL-deficient autosomal recessive osteopetrosis, a very rare skeletal genetic disease in which lack of the essential osteoclastogenic factor RANKL impedes osteoclast formation. The exogenously administered RANKL cytokine is effective in achieving osteoclast formation and function in vitro and in vivo, thus, we produced murine Rankl −/− mesenchymal stromal cells (MSCs) overexpressing human soluble RANKL (hsRL) following lentiviral transduction (LVhsRL). Here, we described a three-dimensional (3D) culture system based on a magnesium-doped hydroxyapatite/collagen I (MgHA/Col) biocompatible scaffold closely reproducing bone physicochemical properties. MgHA/Col-seeded murine MSCs showed improved properties, as compared to two-dimensional (2D) culture, in terms of proliferation and hsRL production, with respect to LVhsRL-transduced cells. When implanted subcutaneously in Rankl −/− mice, these cell constructs were well tolerated, colonized by host cells, and intensely vascularized. Of note, in the bone of Rankl −/− mice that carried scaffolds with either WT or LVhsRL-transduced Rankl −/− MSCs, we specifically observed formation of TRAP + cells, likely due to sRL released from the scaffolds into circulation. Thus, our strategy proved to have the potential to elicit an effect on the bone; further work is required to maximize these benefits and achieve improvements of the skeletal pathology in the treated Rankl −/− mice. Stem Cells Translational Medicine   2019;8:22–34 Abstract :